As sinuosidades e os mistérios das águas: um estudo comparado entre Ruth Guimarães e Itamar Vieira Junior - Cardoso, Viviane dos Santos (Universidade Federal de São Carlos, 2026)
This research aims to conduct a comparative analysis between the novels Água funda (1946), by Ruth Guimarães (1920-2014), and Torto arado (2019), by Itamar Vieira Junior (1979-), especially regarding the presence and influence of two mystical-cultural figures in the novels. In Torto arado, the enchanted Santa Rita Pescadeira participates in and interferes with the main plot actions, in addition to being the narrator of the final part of the work. In Água funda, mysticism is present throughout the plot, but intensifies in the second part of the story, which is dedicated to narrating the madness of the character Joca, which, according to the narrator, was triggered by the apparitions of the Mãe de Ouro. This cultural and religious mysticism is the raw material of a large part of these narratives. Thus, for this comparative analysis, we adopt the parameters of comparative literature, especially the theoretical frameworks of Sandra Nitrini (2021) and Eduardo Coutinho and Tania Franco Carvalhal (1994). Regarding the cultural context of the corpus, we will use Alfredo Bosi (1992), José de Souza Martins (2010), and Stuart Hall (2016, 2024). Finally, to understand the supernatural figures in the plots, we rely on the studies of Câmara Cascudo (1971, 1983, 2012), Cardoso (2023) and Pereira e Silva (2023).
The sinuosities and mysteries of water: a comparative study between Ruth Guimarães and Itamar Vieira Junior
Keywords: Literatura comparada; Ruth Guimarães; Torto arado; Água funda; Itamar Vieira Junior; LINGUISTICA, LETRAS E ARTES::LETRAS::LITERATURA COMPARADA; 4. Educação de Qualidade